The psycholinguistics of translation: Lexical and syntactic processes in Turkish-English context - Kasap, Süleyman; Işık, Nazim (East European Journal of Psycholinguistics, 2025)
This study examines the cognitive processes underlying Turkish-English translation among 41 upper-intermediate English as a Foreign Language (EFL) learners (B2 CEFR) enrolled in an English Language Teaching program. Using a within-subjects design, participants completed lexical (cognates, false friends, low-frequency items) and syntactic (SOV→SVO restructuring) translation tasks while employing think-aloud protocols. Quantitative and qualitative analyses revealed: (1) cognate facilitation (92% accuracy) driven by orthographic-semantic overlap, countered by false friend interference (64% accuracy) requiring inhibitory control; (2) syntactic complexity in restructuring (e.g., relative clauses: 52% accuracy), with prolonged processing times (+40%) reflecting cognitive load; and (3) metacognitive strategies (conceptual monitoring, L1 suppression) as key predictors of success. Findings highlight the interplay of declarative and procedural knowledge in translation, emphasizing pedagogical implications for metacognitive training and corpus-based error analysis in Turkish-English contexts. Disclosure Statement The authors reported no potential conflicts of interest.